Seasonal Evolution of Hydrophilic and Hydrophobic Peptide Contents in Cheeses Made from Ewe's Goat's or Cow's Milk - A. M. Vivar-Quintana; M.A. Blanco López; I. Revilla; I. González-Martín; J. M. Hernández-Hierro; C. González-Pérez (Czech Journal of Food Sciences, 2009)
Proteolysis is the principal and most complex biochemical event occurring during the maturation of the majority of ripened cheese varieties. In addition to softening the cheese body, proteolysis influences the development of cheese flavour via the formation of amino acid and peptides which make a direct contribution to flavour. Goat, cow and sheep cheeses have been elaborated with raw milk and calf rennet. The extent of proteolysis was monitored over six months of ripening and means of HPLC peptide profile analysis. The influence of season on the changes in hydrophobic and hydrophilic peptides and the HO/HI ratio during the ripening of the cheeses were studied.